The Impact of Financial Dollarization on Inflation Targeting: Empirical Evidence from Serbia - Nikola Fabris; Nina Vujanović (Journal of Central Banking Theory and Practice, 2017)
Serbia has applied inflation targeting against the backdrop of financial dollarization for almost a decade. In such circumstances, efficiency of monetary policy instruments decreases and begs the question of efficiency of the monetary regime efficiency issue. Although there is some empirical testing of financial dollarization effects on monetary policy performance in the inflation targeting regime for some countries, such studies for Serbia mostly cover periods of early application of the regime. Therefore, the authors analysed financial dollarization effects on prices, i.e. exchange rate pass-through effect using Serbia as an example. The study concludes that although unpredictable changes in financial dollarization strongly affect nominal exchange rate, prices level is subject to moderate but persistent increase upon this shock.
Keywords: E42; E52; 330; Serbia; financial dollarization; inflation targeting; passthrough effect